Успадкування окремих декоративних і господарсько-цінних ознак сіянцями Astilbe Buch. – Ham. Ex D.Don від спонтанного перезапилення - Буйдін, Ю.В. (Фактори експериментальної еволюції організмів, 2013)
Aims. To investigate features of inheritance of some decorative and economic and valuable signs at a seedlings from spontaneous intercross of varieties of astilbe for the purpose of further use of the received results at creation of domestic varieties. Methods. Were investigated 295 seedlings received from spontaneous intercross of introduced 13 varieties of astilbe. Used comparative morphological and phenological methods. Results. Flowering of seedlings of astilbe in most cases occurs on the second or the third year of vegetation of plants was found out. For the third year flowering was observed in almost at 90 % of studied seedlings was defined. For seedlings from spontaneous intercross of varieties of astilbe have the wide range of inheritance of the main decorative and economic and valuable signs and isn't observed domination of signs of a maternal variety was established. Conclusions. The received results have important theoretical value at a selection of parental couples and can be used during the creation of varieties of domestic breeding.